EDUKASI KETAHANAN EKONOMI DI MASA PANDEMI KEPADA MASYARAKAT KELURAHAN WONOBOYO, KECAMATAN WONOGIRI TAHUN 2020 - Devina Melinawati; M.Rifky Ariyo Suseno (LPPM STAIMAS WONOGIRI, 2021)
The spread of the Covid-19 outbreak requires the government to immediately act to carry out various efforts such as Large-Scale Social Restrictions (PSBB), working from home, the obligation to use masks, etc. It is difficult to change the pattern of behavior that has become a habit of society in general into a new habit that is much different in a short time. Wonoboyo Village is one example of an area affected by the pandemic that hit the micro economy. Socialization and education are one of the efforts that will be made to the local community as a tangible form of service that aims to invite the community to intensely implement health protocols as an effective step to prevent COVID-19 and maintain economic resilience during the pandemic. The method to achieve the goal of this service is socialization, demonstration, and interactive dialogue which is carried out through activity programs regarding Covid-19 prevention, community habituation in the new normal era, and community economic resilience. After participating in this series of programs, the community always implements health protocols, feels calmer, and can manage finances to realize family economic resilience. Although this service activity is only carried out within the scope of the village, the impact on the community is very high. The community is very enthusiastic in supporting this service program because the benefits have been directly felt by them.